2019
DOI: 10.3166/phyto-2019-0164
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Antinociceptive, and Antioxidant Potentials of Algerian Zizyphus jujuba Mill. Fruits and Leaves In Vivo and In Vitro in Different Experimental Models

Abstract: The ethanolic extracts of the aerial parts, leaves, and fruits, of Zizyphus jujuba Mill. were studied in vivo and in vitro for their anti-inflammatory, analgesic, and antioxidant properties, respectively. A preliminary phytochemical screening was carried out. It revealed the presence of several phytoconstituents such as flavonoids, phenols, and alkaloids. The acute toxicity study was conducted using a limit dose of 2,000mg/kg. The extracts studied showed no signs of toxicity or mortality. Anti-inflammatory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Özgan ( 41 ) in a study investigating the possibilities of using grape seed oil in laying hens, reported that they thought that β-ovomucin in the structure of albumen was protected thanks to the antioxidant properties of this oil and accordingly, albumen height could increase. Many studies ( 13 , 14 , 42 , 43 ) have reported that jujube leaf extract has antioxidant properties. Based on this information, it can be said that JLE increased the albumen index and Haugh unit in the present study due to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Özgan ( 41 ) in a study investigating the possibilities of using grape seed oil in laying hens, reported that they thought that β-ovomucin in the structure of albumen was protected thanks to the antioxidant properties of this oil and accordingly, albumen height could increase. Many studies ( 13 , 14 , 42 , 43 ) have reported that jujube leaf extract has antioxidant properties. Based on this information, it can be said that JLE increased the albumen index and Haugh unit in the present study due to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Jujube is a medicinal plant in the Rhamnaceae family ( 12 ). Studies ( 13 , 14 ) have shown that the leaves of this plant are important as antioxidants. There are a limited number of studies on the use of Zizyphus jujuba leaves in animal nutrition.…”
Section: Introductionmentioning
confidence: 99%